1990
DOI: 10.1093/nar/18.15.4427
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of human and murine snRNP proteins by two-dimensional gel electrophoresis and phosphopeptide analysis of U1-specific 70K protein variants

Abstract: The proteins of the major human snRNPs U1, U2, U4/U6 and U5 were characterised by two-dimensional electrophoresis, with isoelectric focussing in the first dimension and SDS-polyacrylamide gel electrophoresis in the second. With the exception of protein F, which exhibits an acidic pl value (pl = 3.3), the snRNP proteins are basic. Post-translational modification was found among the proteins associated specifically with the U1 and U2 particles. The most complex modification pattern was observed for the U1-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 40 publications
0
47
0
1
Order By: Relevance
“…On the basis of comparisons with published two-dimensional gels {Feeney et Woppmann et al 1990), however, we do detect lower molecular weight proteins that are likely to correspond to the known snRNP core proteins (C, D, E, F, and G; data not shown). Notably, other than these proteins, we do not detect significant levels of any other lower molecular weight proteins.…”
Section: Genes and Developmentmentioning
confidence: 60%
“…On the basis of comparisons with published two-dimensional gels {Feeney et Woppmann et al 1990), however, we do detect lower molecular weight proteins that are likely to correspond to the known snRNP core proteins (C, D, E, F, and G; data not shown). Notably, other than these proteins, we do not detect significant levels of any other lower molecular weight proteins.…”
Section: Genes and Developmentmentioning
confidence: 60%
“…Interestingly, of the two U1-70K isoforms observed in whole cell extracts, only the more rapidly migrating U1-70K species was identified in the pull-down experiments. As U1-70K is known to be phosphorylated (Tazi et al, 1993;Woppmann et al, 1990), we suspected that the more rapidly migrating form might be dephosphorylated. Consistent with this notion, we found that phosphatase treatment of the embryonic extracts prior to western blot analysis resulted in a single U1-70K species with a similar mobility to the protein detected in the pull down experiments (data not shown).…”
Section: Sxl Associates With U1 Snrnp Particles In Whole Cell Extractsmentioning
confidence: 99%
“…It is thought that the Ser residues in the RS domains of SR proteins become phosphorylated, since all are phosphoproteins (Krainer et al, 1991;Zahler et al, 1992) and the analogous domain in U1-70K is phosphorylated at multiple serines in vivo (Woppmann et al, 1990). Moreover, synthetic random co-polymers of Arg and Ser are excellent substrates for many Ser/Thr protein kinases (Racker, 1991).…”
Section: Introductionmentioning
confidence: 99%